Stalin and the Spanish Civil War - Kowalsky, Daniel, 1966-; American Council of Learned Societies ([New York] : Columbia University Press, 2008)
Kowalsky's study presents a critical reassessment of the role of Jos ef Stalin and the Soviet Union in the Spanish Civil War. Employing a wi de range of declassified Soviet documents, other unpublished materials of Spanish provenance, published memoir accounts, previously unseen cin ematic evidence, poster art, and sound recordings, Kowalsky argues that though Stalin's intervention in Spain was enormously ambitious, it was an operational failure of roughly the same scale. The text is accompan ied by appendices of images, video clips, and reproductions of archival documents.
Caption title; description based on screen of 2008-04-30.
Originally published by Gutenberg-e: www.gutenberg-e.org.
Includes bibliography.
Electronic text (HTML) and image data (JPG).
This volume is made possible by a grant from the Andrew W. Mellon Fo undation.
Mode of access: Intranet.
Keywords: Stalin, Joseph, -- 1879-1953.; Spain -- History -- Civil War, 1936-1939 -- Participation, Russian; Soviet Union -- Foreign relations -- 1917-1945.; Spain -- Foreign relations -- 1931-1939.